The modernization of European cohesion policy - Peter Becker (Stiftung Wissenschaft und Politik (SWP), 2009)
Cohesion Policy has become one of the European Union's central policy concerns since the mid-1980s. But this Community policy is subject to unyielding pressure to adapt and reform. Hardly have the principles, objectives, funds, priorities and administrative procedures been agreed for one funding period, than the next reform debate begins. In the latest discussions there are two opposing models for Cohesion Policy:a. Traditional structural policy looking to promote the most backward regions in the EU. b."Lisbonized" policy aiming to increase competitiveness, growth and employment. The two models differ fundamentally with respect to their goals and instruments, their legal basis and priorities, and the beneficiaries and interests involved. The current reform of Cohesion Policy will have to find a compromise between "Lisbonized" priorities and the traditional treaty-anchored goals of solidarity and regional cohesion. Thoughts should revolve around pragmatic advances and adaptations, remaining in those realms where compromise solutions are absolutely plausible.From the German perspective Cohesion Policy must concentrate more strongly on priority goals and regions and be implemented in accordance with the principles of subsidiarity in order to ensure a funding policy that is effective, targeted and tailored to the needs of the recipients. Where it is necessary to choose between flexible implementation (associated with weakened monitoring and reporting requirements) and greater effectiveness of Cohesion Policy, Germany as the biggest net payer in the EU should work for more efficient use of scarce resources
Keywords: 320